Community perspectives on HIV, violence and health surveillance in rural South Africa: a participatory pilot study - Nitya Hullur 1; Lucia D'Ambruoso 1,2; Kerstin Edin 2,3; Ryan G Wagner 2,3,4; Sizzy Ngobeni 3; Kathleen Kahn 2,3; Stephen Tollman 2,3,4; Peter Byass 1,2,3 (Edinburgh University Global Health Society, 2016)
South Africa faces a complex burden of disease consisting of infectious and non-communicable conditions, injury and interpersonal violence, and maternal and child mortality. Inequalities in income and opportunity push disease burdens towards vulnerable populations, a situation to which the health system struggles to respond. There is an urgent need for health planning to account for the needs of marginalized groups in this context. The study objectives were to develop a process to elicit the perspectives of local communities in the established Agincourt health and socio-demographic surveillance site (HDSS) in rural north-east South Africa on two leading causes of death: HIV/AIDS and violent assault, and on health surveillance as a means to generate information on health in the locality.